Flow dynamics of Nankai Trough submarine landslide inferred from internal deformation using magnetic fabric. (30th October 2014) - Kanamatsu, Toshiya; Kawamura, Kiichiro; Strasser, Michael; Novak, Beth; Kitamura, Yujin
Abstract Submarine landslide deposits in an active subduction zone were investigated by Integrated Ocean Drilling Program Expedition 333 as the "Nankai Trough Submarine Landslides History." The expedition recovered a Pleistocene to Holocene sequence of stacked mass‐transport deposits at Site C0018, located within a slope basin on the footwall of the megasplay fault in the Nankai Trough off the Kii Peninsula, southwest Japan. Six mass‐transport deposit units intercalated with coherent intervals were recovered from the upper 190 m of the drilled succession. Anisotropy of magnetic susceptibility variations within mass‐transport deposit units was used to ascertain their rheology. Shape parameters and magnetic fabric orientation reveal inhomogeneity through the sequences, indicating that different compaction and shear occurred within individual units. The upper intervals of younger units generally represent a magnetic fabric formed under vertical compression. However, the lower intervals involve magnetic fabrics indicating lateral shear with in‐depth gradual change. In the older mass‐transport deposit, a distribution of magnetic foliation forms tightly folded strata, indicating different sliding patterns from the younger mass‐transport deposit units. Using available paleomagnetic data, the shear directions of basal intervals of units are reoriented, producing two different sliding orientations. Variation in the flow type and supply route is interpreted to reflect the slope condition (e.g., slope gradient and susceptibility to ground motion), which has been controlled by local tectonic evolution of the accretionary wedge.